Organizational Structure and Business Growth of Pharmaceutical Industry in Delta State, Nigeria - Okolie, Ugo Chuks; Omogbiya, Oghenenyerhowvo Shulammite; Addah, Grace Aruoriwo-oghene (Universitas Pendidikan Indonesia, 2023)
This study examined influence organisational structure on business growth of pharmaceutical industry in Delta State. A cross-sectional research design and convenience sampling technique were adopted. A questionnaire was employed as the research instrument for this study with 109 respondents deemed usable. The autopoietic systems theory was used to explain how organisational structure might enhance business growth in Nigerian manufacturing firms. Statistical Package for Social Sciences (SPSS) software version 23.0 was used to perform descriptive and inferential statistics, correlation analysis, and simple regression analysis on the collected data.The results of the study revealed that organisational structure has a very strong positive and significant relationship with business growth. The study confirmed what was expected by demonstrating that organisational structure has a positive, significant impact on the expansion of the pharmaceutical sector in Delta State. The study's findings suggest that, in order to improve business growth, management in Nigeria's pharmaceutical industry should create the proper organisational structures to increase worker productivity and working conditions. In order to promote business growth, the study advises management in the Nigerian pharmaceutical industry to use formalised, a lower layer of organisational hierarchy, technology, and loose boundaries.